Economic and Societal Losses Due to Environmental Impacts on Forestry Productivity (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
After successful government-led afforestation projects, what are the challenges for forest management in the face of climate change in East Asia? This reprint presents studies from the natural and social sciences related to forest conservation, engineering, disaster sociology, and forest policy in China and Japan. The papers cover a range of topics, including forest owners' attitudes, forest resource utilization, evaluation of forestry mechanization and forest roads, characteristics of damage from torrential rains, resilience of rural communities, economic transformation, and others.